Optimalisasi Akad Mudharabah Dalam Perbankan Syariah - Ach Faqih Supandi (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2019)
The principle of mudharabah is a unique part of Islamic banking products, because it has a philosophical difference between the conventional banking system and Islamic banking which adheres to the principle of profit or loss. Mudharabah is a partnership business covering capital owners (Shahib al-mal) and business actors (mudharib), aiming to gain profit (al-ribh) and divided according to agreement in the contract. This research is library research. While this research approach uses a statute approach, because the problems in this study are approached with positive legal norms and Islamic law. The purpose of writing scientific papers is to determine the extent to which Islamic banking in optimizing Mudharabah contracts as products in Islamic banking. The results of this study are one of the institutions that can guarantee the continued maintenance of compliance with Sharia or Islamic law is the DSN-MUI which gives sharia compliance compliance authorities (Shariah Compliance) is the Sharia Supervisory Board (DPS). The implementation of the Mudharabah contract in the Islamic banking system is one form of banking compliance with the sharia principles that DPS-MUI has applied to Islamic banking.